The interpretation of logophoric and ordinary pronouns in Ewe: an experimental study - Silleresi, Silvia; Bassi, Itai; Bimpeh, Abigail Anne; Driemel, Imke; Nuworsu, Anastasia; Guasti, Maria Teresa (Proceedings of the Amsterdam Colloquium, 2024)
This study examines the interpretation of logophoric and ordinary pronouns in Ewe. While the logophor yè is predicted to obligatorily refer to the attitude holder in indirect speech reports, the ordinary pronoun’s reference pattern remains debated. Thirty-eight Ewe speaking adults completed an acceptability judgment task evaluating pronoun usage in self and anti-self contexts for communicative (say) and mental (think) verbs. The findings align with the principle of Maximize Presupposition, assuming yè encodes a presupposition: yè is preferred when its presupposition is met, blocking the occurrence of the ordinary pronoun é. In turn, é is favored only where the presupposition of yè fails, though less robustly than yè.